2022
DOI: 10.1038/s41598-022-24784-4
|View full text |Cite
|
Sign up to set email alerts
|

A cost-utility analysis between decompression only and fusion surgery for elderly patients with lumbar spinal stenosis and sagittal imbalance

Abstract: Lumbar spinal stenosis (LSS) and sagittal imbalance are relatively common in elderly patients. Although the goals of surgery include both functional and radiological improvements, the criteria of correction may be too strict for elderly patients. If the main symptom of patients is not forward-stooping but neurogenic claudication or pain, lumbar decompression without adding fusion procedure may be a surgical option. We performed cost-utility analysis between lumbar decompression and lumbar fusion surgery for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…They will be used in a separate study to develop evidence-based recommendations for economic evaluations in spine surgery. Finally, a total of 130 clinical cost-effectiveness studies were included 24–153…”
Section: Resultsmentioning
confidence: 99%
“…They will be used in a separate study to develop evidence-based recommendations for economic evaluations in spine surgery. Finally, a total of 130 clinical cost-effectiveness studies were included 24–153…”
Section: Resultsmentioning
confidence: 99%
“…Our results also extend those of Alvin et al, 42 who, in a single-institutional cohort of patients undergoing DA or DF (further stratified by type of fusion), also found that each subtype of DF had an ICER greater than $800,000 USD or was strongly dominated by DA over a one-year time horizon. Finally, in a single-institutional assessment of 71 patients undergoing DA or DF in South Korea, Won et al , 43 estimated an ICER of $49,833 over a two-year time horizon. These results are not directly comparable with our own—patients in this study met criteria for LSS and sagittal-plane deformity and therefore may represent a subset of LSS patients who would not be well served with DA alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, extreme care should be taken not to decide on a surgical formula based on diagnosis from static imaging alone [ 8 ]. Decision-making and treatment options for LSS with sagittal imbalance are still controversial [ 9 ]. In fact, significant improvement of sagittal spinopelvic alignment has been known after simple lumbar decompression surgery for LSS [ 10 ].…”
Section: Discussionmentioning
confidence: 99%